Efficacy and safety of three species of Rhodiola L. in patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis - Yu, Haichuan; Lei, Ting; Su, Xiaojie; Zhang, Lu; Feng, Zhouzhou; Dong, Mengya; Hou, Zheyu; Guo, Hong; Liu, Jian (Frontiers in Pharmacology, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by chronic hypoxia, inflammation, oxidative stress, and irreversible airflow limitations. Rhodiola L. is a genus of botanical drugs used in traditional medicine that may influence COPD. Objective: A systematic review of the safety and efficacy of Rhodiola L. in patients with COPD. Material and methods: We searched the PubMed, Embase, Cochrane Library, Web of Science, Scopus, China National Knowledge Infrastructure (CNKI), Chongqing VIP, Wanfang, and SinoMed databases. The search strategy used terms including “COPD” and “Rhodiola.” Two independent reviewers conducted the literature screening, data extraction, and risk of bias assessment, with a third reviewer involved to resolve disagreements. Statistical analysis was conducted in Review Manager (version 5.4.1), following the Cochrane Handbook. Results: This review included nine studies, of which two focused on Rhodiola crenulata (Hook.f. and Thomson) H. Ohba (R. crenulata) and two on Rhodiola kirilowii (Regel) Maxim (R. kirilowii); the remaining five focused on Rhodiola wallichiana (Hook.) S.H.Fu (R. wallichiana). Compared with the placebo, patients who received Rhodiola L. presented no more adverse events (p = 0.65) but showed significant improvement in the percentage of forced expiratory volume in 1 s at prediction (FEV1%pred), forced expiratory volume in 1 s (FEV1), the ratio of forced expiratory volume in 1 s on forced vital capacity (FEV1/FVC), saturation of oxygen in arterial blood, partial pressure of oxygen in arterial blood (PaO2), partial pressure of carbon dioxide in arterial blood (PaCO2), systolic pulmonary arterial pressure, diastolic pulmonary arterial pressure, COPD assessment test, efficient rate, C-reactive protein, and N-terminal pro-B-type natriuretic peptide (all p < 0.01). Compared with ambroxol, R. kirilowii provided additional benefits to patients with COPD in FEV1%pred, FEV1, FEV1/FVC, PaO2, PaCO2, 8-iso-prostaglandin F2α, superoxide dismutase, glutathione, malondialdehyde, and total antioxidant capacity (all p < 0.01). Conclusion: Among the Rhodiola L. genus, this review included R. wallichiana, R. crenulata, and R. kirilowii, which might be safe and effective in COPD. Although this study has several limitations, further RCTs are needed. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/ display_record.php?RecordID=302881], identifier [CRD42022361890].